Suppression of CD13 Enhances the Cytotoxic Effect of Chemotherapeutic Drugs in Hepatocellular Carcinoma Cells - Ji, Shengping; Ma, Yuqian; Xing, Xiaoyan; Ge, Binbin; Li, Yutian; Xu, Xinyue; Song, Jiliang; Xiao, Mei; Gao, Feng; Jiang, Wenyan; Fang, Chunyan; Wang, Xuejian (Frontiers in Pharmacology, 2021)
Multidrug resistance (MDR) in hepatocellular carcinoma (HCC) is a profound phenomenon which hinders the efficacy of chemotherapeutic drugs. In this study, we explore MDR in relation to reactive oxygen species (ROS)-induced CD13 expression in HCC cells. We show that fluorouracil (5-FU), gemcitabine (GEM), and epirubicin (EPI) can induce ROS generation, activate Ets2 and promote CD13 expression. Simultaneously, CD13 can activate nuclear factor-erythroid 2-related factor 1 (NRF1) and up-regulate transcription of ROS scavenging genes, such as SOD1, GPX1, GPX2 and GPX3, leading to down-regulation of intracellular ROS level and reducing the sensitivity of cells to chemotherapeutic drugs. We also examined the anti-tumor effect of the combination therapy using CD13 inhibitor ubenimex and a variety of conventional anti-cancer drugs, such as 5-FU, GEM, EPI, pemetrexed (Pem), and paclitaxel (PTX). Ubenimex enhances the sensitivity of HCC cells to different chemotherapeutic agents and suppresses tumor cell growth both in vitro and in vivo. Our study suggests that overexpression of CD13 can lead to chemotherapeutic drug resistance, and CD13 inhibitor can reverse this effect. Therefore, combination of chemotherapeutic drugs with CD13 inhibitor such as ubenimex could be a potential treatment strategy for overcoming MDR in liver cancer.